(untitled) (Stamford Journal of Microbiology, 2015)
Present study assessed the microbiological quality of different categories of consumable potatoes collected from Bangladesh Agricultural Research Institute (BARI), the largest multi-crop research institute of the country conducting research on a large number of crops. Five samples each from 15 categories of potato samples (Lara, Quincy, Cardinal, Esprit, Meridian, Lady Rossetta, Astrix, Soikat, Red potato, White potato, Russet potato, Yellow flesh potato, Sweet potato, Purple potato and Petiets potato) were subjected to microbiological analysis through conventional culture followed by the biochemical identification tests of the pathogens. A huge array of bacterial and fungal contamination was noticed within a range of ( 108 cfu/g) in almost all samples studied. Among the bacterial pathogens, Escherichia coli and Staphylococcus spp. were found to be predominant. Study of antibiogram revealed that most of the isolates were resistant against the commonly used one or multiple antibiotics. Finally, all the samples were also examined for presence of any anti-microbial activity against different pathogenic bacterial species. Astrix potato samples exhibited antimicrobial activity against Shigella spp and the Russet potato samples exhibited the anti-bacterial activity against Staphylococcus spp. DOI: http://dx.doi.org/10.3329/sjm.v3i1.22747 Stamford Journal of Microbiology, Vol.3(1) 2013: 21-25